The Effect of Accessibility and Destination Image on Intention to Visit Again. (Case Study on Batu Malin Kundang Tourism Object at Air Manis Beach Padang) - Syofria Meidona (Enrichment : Journal of Management, 2022)
This study aims to determine the effect of accessibility and destination image have a positive and significant simultaneous effect on the intention to revisit the Batu Malin Kundang tourist attraction at Air Manis Beach Padang. The sample was selected using the incidental sampling method. The sample used was 30 respondents. The data collection technique used a questionnaire, while the data analysis method used validity and reliability tests, classical assumptions, multiple linear regression analysis and statistical tests (T test, F test and coefficient of determination). The results showed that the accessibility variable on the intention to revisit the Batu Malin Kundang tourist attraction at Air Manis Beach Padang with a Tcount value of 3.199 at a significant level of 0.004 <0.05, so it can be concluded that the first hypothesis is accepted, the results of the study show that the destination image variable towards intention to return to Batu Malin Kundang tourist attraction at Air Manis Beach Padang with a tcount value of 3.338 at a significant level of 0.002 < 0.05, so it can be concluded that the second hypothesis is accepted, the results of the study indicate that the variable accessibility and destination image simultaneously affect the intention to revisit at Batu Malin Kundang tourist attraction on Air Manis Beach Padang, the value of Fcount = 27.232 with sig = 0.000 <0.05. The results of calculations using the SPSS V23 program can be seen that the coefficient of determination R2 = 0.669. This means that 66.9% of revisit intentions can be explained by accessibility variables and destination image, while the remaining 33.1% value of revisiting intentions is influenced by other variables not examined in this study.